Evidences of the Intensity of the Balassa-Samuelson Phenomenon in the Romanian Economy - Moisa Altar; Lucian Liviu Albu; Ionut Dumitru; Ciprian Necula (Romanian Academy, National Institute for Economic Research, 2009)
The paper presents some results revealing the existence of the Balassa-Samuelson effect in Romania as well as some estimates of its impact on inflation, appreciation of the real exchange rate and rising competitiveness of the Romanian economy. * Study within the CEEX Programme Project No. 220/2006 Economic Convergence and Role of Knowledge in Relation to the EU Integration ; Instiutul European din Romania PAIS III; Studiul nr. 2/2005.
Keywords: F33; O23; O24; O47; 330; Balassa-Samuelson effect; exchange rate; inflation; competitiveness